In my time of dying : a history of death and the dead in West Africa - Parker, John, 1960- (Princeton University Press, 2021)
"Why do people die and where do they go when they are dead? How should the dead be buried and mourned in order to ensure that they continue to work for the benefit of the living? How have perceptions and experiences of death and the ends of life changed over the centuries? In My Time of Dying considers these questions from the perspective of African history. In what is the first history of death in Africa, John Parker examines mortuary culture and the ongoing relationship between the living and the dead over a four-hundred year period. Focusing anecdotally on West Africa but with a comparative awareness of comparable practices throughout the continent, Parker highlights how Africans developed the world's most vibrant and recognizable cultures of death"--